Assessment of the application for renewal of authorisation of manganese chelate of hydroxy analogue of methionine for all animal species. (12th November 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the application for renewal of authorisation of manganese chelate of hydroxy analogue of methionine (Mintrex ® Mn) for all animal species. The FEEDAP Panel has delivered three opinions (in 2008, 2009 and 2010) on the safety and efficacy of the additive. The additive was authorised in 2010 as 'Manganese chelate of hydroxy analogue of methionine' containing 15.5−17 % manganese, 77−78 % (2‐hydroxy‐4‐methylthio)butanoic acid (dl ‐Methionine Hydroxy Analogue, HMTBa) and maximum 1% mineral oil. Following some modifications in the manufacturing process the additive does not contain mineral oil and the applicant proposes the following specifications: ≥ 14 % manganese and ≥ 76 % HMTBa. The data provided indicate that the additive complies with the new specifications. No new evidence was found that would make the FEEDAP Panel reconsidering its previous conclusions on the safety for target species, consumers and environment. The applicant provided new studies on the effects of the additive on the respiratory tract and on skin and eyes. Data on the characterisation of the additive and the new studies on skin/eyes led the Panel to reconsider the safety for the user. Owing to the manganese and nickel content of Mintrex ® Mn, the handling of the additive poses a risk to users by inhalation; the additive is not a skin or eye irritant but is considered as a skin sensitiser. The present application did not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive; therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.